2020
DOI: 10.1111/jiec.13057
|View full text |Cite
|
Sign up to set email alerts
|

Nestedness of eco‐industrial networks: Exploring linkage distribution to promote sustainable industrial growth

Abstract: Eco‐industrial networks (EINs, of which eco‐industrial parks are a subset) have gained support as a solution that simultaneously reduces environmental burdens and promotes economic interests. EINs operate under a mutualistic framework, where waste materials and energy are exchanged between industries to their mutual benefit, creating a diverse web of flows. Recent studies have focused on analogies between food webs (FWs) and EINs, measuring a network's success at ecological imitation as representative of its s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…The research of Brehm and Layton (2021) focused on the metric of nestedness, which is an ecological approach that resorts to the placement of linkages between nodes in a network to maximize network cyclicity for a given number of links. This measure provides numerous benefits for the design and study of EINs (Eco-Industrial networks), including maturity independence, size normalization, and strong statistical documentation of ecological systems with a high degree of mutualism.…”
Section: Cluster : Eco-industrial Parksmentioning
confidence: 99%
“…The research of Brehm and Layton (2021) focused on the metric of nestedness, which is an ecological approach that resorts to the placement of linkages between nodes in a network to maximize network cyclicity for a given number of links. This measure provides numerous benefits for the design and study of EINs (Eco-Industrial networks), including maturity independence, size normalization, and strong statistical documentation of ecological systems with a high degree of mutualism.…”
Section: Cluster : Eco-industrial Parksmentioning
confidence: 99%
“…In 2019, Alves et al studied the nestedness of global production network with intercountry input-output data and discussed about the contribution of various countries and industries to nestedness, as well as the influence of nested structure in global economy [13]. In 2020, by comparing various network indicators of predatory networks and ecoindustrial park networks, Colton et al found a positive correlation between the nestedness and periodicity of eco-industrial park networks, thus providing specific suggestions for the industrial layout and infrastructure construction in the park [14].…”
Section: Literature Reviewmentioning
confidence: 99%
“…ENA metrics can then be calculated using T. In this section, the ENA modeling process and the DoSO metric are elaborated, focusing on the notional SoS architectures used in this study. Interested readers may refer to previous work, which has adapted ENA for applications in industrial networks, [66][67][68][69][70][71] power grids, 72 water distribution networks, 73,74 and supply chains. 75 Consider the architecture presented in Figure 3(C).…”
Section: Sos Architectures' Doso Evaluationmentioning
confidence: 99%